Single-shot carrier-envelope-phase tagging using an f-2f interferometer and a phase meter: A comparison - Ren, Xiaoming; Summers, A. M.; Raju, Kanaka P.; Vajdi, Aram; Makhija, Varun; Fehrenbach, C. W.; Kling, Nora G.; Betsch, K. J.; Wang, Zhenhua; Kling, M. F.; Carnes, K. D.; Ben-Itzhak, I.; et al. (Journal of Optics, 2017)
Carrier-envelope phases (CEPs) from a kHz repetition rate, non-CEP stabilized laser system are measured and tagged with two different methods: an f-2f interferometer and a stereo-above-threshold-ionization carrier-envelope-phase-meter. Both methods utilize the octave spanning spectrum generated in the hollow-core fiber (HCF) that broadens the laser spectrum to produce few-cycle pulses. Phases from both methods are carefully synchronized and compared on a single shot level. The results show that the CEPs measured by both methods are in good agreement and demonstrate that a HCF based f-2f interferometer is well suited for CEP tagged experiments.
CRIS-Team Scopus Importer:2023-04-20
Keywords: carrier envelope phase tagging; few-cycle pulses; ultrafast science